Carl Menger and the evolution of payments systems : from barter to electronic money - Latzer, Michael; Schmitz, Stefan W. (Cheltenham, UK ; Northampton, MA, USA E. Elgar Pub., 2002)
This title on Menger and the history of economic thought develops Menger's analysis of transactions so as to illuminate and advance discussions on the prospects for electronic money, an important topic in contemporary monetary theory.
Includes bibliographical references and index.
rpm 25/08/16
Loans
Keywords: Menger, Carl; Money; Payment; Electronic funds transfers